2005
DOI: 10.1017/s0959259805001668
|View full text |Cite
|
Sign up to set email alerts
|

Elder abuse

Abstract: Elder neglect and abuse is a widespread, largely undiagnosed and often ignored problem in our society. However, recently elder abuse has gained increasing recognition as a significant problem, meriting the attention of both clinicians caring for older people and society at large. Its occurrence in differing forms throughout the world has been highlighted as part of a recent WHO report about violence and health. In the United Kingdom, the House of Commons Health Committee has inquired into elder abuse and publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…Nowadays, it is viewed as a public health problem, particularly since older adults' abuse has been associated with higher rates of morbidity (Kleinschmidt, 1997). Notwithstanding this increase of interest, the field of abuse of older adults still remains the least acknowledged of the types of human violence (O'Connor and Rowe, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, it is viewed as a public health problem, particularly since older adults' abuse has been associated with higher rates of morbidity (Kleinschmidt, 1997). Notwithstanding this increase of interest, the field of abuse of older adults still remains the least acknowledged of the types of human violence (O'Connor and Rowe, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Emotional abuse refers to behaviour by someone who is trusted by the elder that inflicts mental pain and stress via verbal or nonverbal means. 9,18,25 The prevalence of psychological abuse was reported to be 4.2% by Oh et al, 10 7.2% by Pavlik et al, 31 9% by Anme, 26 and the prevalence of verbal abuse was 26.8% according to Yan and Tang. 25 In a systematic review that aimed to determine the prevalence of elder abuse and neglect, it was found that nearly one fourth of the more fragile/defenceless elders in the general population were subjected to psychological abuse and that 16% of nursing home staff admitted to inflicting psychological abuse.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] Like other types of abuse, elder abuse is also a complex 11,15 and multifactorial condition, which can be considered as a geriatric syndrome. 18 The prevalence of abuse is particularly higher among fragile, lonely, or depressed older adults in addition to those who have a physical disability or mental illness. 19 The prevalence of hidden problems such as elder abuse and neglect increases in parallel to the expanding older population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The team began its project by educating itself about the nature of elder abuse, learning that it is frequently overlooked as a critical safety issue in contemporary society, and is considered one of the least acknowledged types of interpersonal violence (O’Connor & Rowe, 2005, p. 47). The team worked from a definition of elder abuse as (a) intentional actions that cause harm or create a serious risk of harm (whether or not harm is intended), to a vulnerable elder by a caregiver or other person who stands in a trust relationship to the elder, or (b) failure by a caregiver to satisfy the elder’s basic needs or to protect the elder from harm.…”
Section: Par In An Urban Norcmentioning
confidence: 99%